Doorknob in the desert: Agnes Martin's queer becoming. (1st April 2016) - Cook, Roger
Alongside recent knowledge of her schizophrenia, Agnes Martin's lesbianism and its relation to her extraordinary achievement as an artist needs to be better understood. Anterior to activist Monique Wittig's infamous 1978 public statement that 'lesbians are not women' (Wittig 1993: 32), in 1973 Martin (refusing compulsory heterosexuality's sex and gender dimorphism) humorously protested that she 'was not a woman but a doorknob' (Johnston 1998: 300). Ultimately, Martin's liberation was a liberation through identification with non-human being: a painterly practice of queer becoming that can be thought of as the Foucauldian creation of life as a 'work of art' – a desubjectivization of the self or 'death of the subject' enacting a Barthesian 'desire for the neutral' (Barthes 2005) to become one with the vitality and vibrancy of matter itself.